The Rat Homolog of the Schizophrenia Susceptibility Gene ZNF804A Is Highly Expressed during Brain Development, Particularly in Growth Cones. - Katja Hvid Hinna; Karen Rich; Åsa Fex-Svenningsen; Eirikur Benedikz (PLoS ONE, 2015)
A single nucleotide polymorphism in the ZNF804A gene, rs1344706, is associated with schizophrenia. The polymorphism has been suggested to alter fetal expression of ZNF804A. It has also been reported to be associated with altered cortical functioning and neural connectivity in the brain. Since developmental mechanisms are suggested in the pathophysiology for schizophrenia, expression of Zfp804A, the rat homolog of ZNF804A, was investigated in the developing rat brain. We found that expression of Zfp804A in most brain regions is developmentally regulated and peaks around birth, where after it decreases towards adult levels. This time point is developmentally the equivalent to the second trimester of fetal development in humans. An exception to this expression pattern is the hippocampus where the expression of Zfp804A appears to increase again in the adult brain. Using laser capture and quantitative PCR we found that Zfp804A mRNA expression in the adult rat hippocampus is highest in the CA1 sub region, where the overall firing rates of neurons is higher than in the CA3 region. In cultured cortical neurons Zfp804A mRNA expression peaked at day 4 and then decreased. The ZFP804A protein expression was therefore investigated with immunochemistry in such cultures. Interestingly, before day 4, the protein is mostly found in the perinuclear region of the cell but at day 4, ZFP804A was instead found throughout the cell and particularly in the growth cones. In conclusion we demonstrate that Zfp804A increases in the rat brain at the time of birth, coinciding with neuronal differentiation. We also show that ZFP804A is localized to growth cones of growing neurites. These data implicate ZFP804A in growth cone function and neurite elongation. The polymorphism rs1344706 lowers expression of ZNF804A during prenatal brain development. This may affect ZNF804A's role in cone function and neurite elongation leading to synaptic deficits and altered neural connectivity.